THE INFLUENCE OF JOB TRAINING AND CAREER DEVELOPMENT ON JOB SATISFACTION AND ITS IMPLICATIONS FOR PRODUCTIVITY - Mardiyana, Mardiyana; Hidayat, Rahmat (Universitas Pembinaan Masyarakat Indonesia, 2023)
Effect of job training and career development on job satisfaction and its implications for productivity. This type of research uses a quantitative type. The number of samples is 85 employees who work in Sukahurip Village. The data used in this study are primary and secondary data, namely the distribution of questionnaires and through Google forms to Sukahurip Village Officials. The research uses the Lisrel data processing application version 8.8. The results of this study are job training has no effect on job satisfaction, career development has no effect on job satisfaction, job training has no effect on productivity, career development has an effect on productivity, job satisfaction has no effect on productivity, career development and job training simultaneously affect job satisfaction. Job satisfaction, job training, and career development simultaneously affect productivity. JEL Classification: M21, O15, O17